(3GdhGVM aj TQM eNJUQ CHj GdbGSe GdNQbis - (3fhQ GdOjf CHh WGdH YHO GdQMef Hf YeQ Hf CHj GdbGSe GdHUQj GdVQjQ, GHf CHj GdbGSe,J (B684 (3g` s ((3GdeOQSI GdeSJfUQjI(B-(3HZOGO s)
(3ChdgG (B:s
(3hgh GdUMjM dCf GdbUO efg GdbSe GdKGfi fLGSI ZjQ GdcdH hGdNfRjQ s
(3BNQgG (B:s
(3BNQ GdeLdO GdChd hgh cJGH GdhGVM ai TQM GdNQbi hjJdhg ai GdKGfi ef cJGH GdhOjYI Ef TGA Gddg JYGdi s
(3ai BNQgG eG jOd Ydi CfgG ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B93s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs